First discovery – and a new species – of Coelogynopora (Platyhelminthes, Proseriata) in the Southern Hemisphere - Volonterio, Odile; Ponce de León, Rodrigo (European Journal of Taxonomy, 2021)
Coelogynoporidae (Platyhelminthes) includes comparatively large and slender Proseriata, usually occurring in shallow benthic environments. Coelogynopora Steinböck, 1924 is the most frequently reported genus and the one with the highest species diversity. Notwithstanding that, the genus has never been reported from the Southern Hemisphere. A recent analysis of sediment from the Magellan Strait shores (Chile) resulted in the discovery of a new species of Coelogynopora, the first representative of the genus to be found in austral waters. The new species is defined by the following combination of characters: sclerotised copulatory system consisting of a slender, ventrally curved stylet with a broad base and three pairs of symmetrically arranged spines, the proximal ends of which are fused laterally to the base of the stylet; distal ends of the three pairs of spines hooked, with apophyses at progressively longer distances from the tip; accessory spines and solar organ absent. Based on the morphological characters, the new species appears to be more related to species from the Pacific Ocean than to those from the Atlantic Ocean. The present work suggests a vast biogeographic disjunction in the genus Coelogynopora, which may be described as a bipolar or amphitropical pattern of distribution.